Tolerance and determinants of drought character descriptors of the Madurese landrace bambara groundnut (Vigna subterranea) - Siti Fatimah; ARIFFIN ARIFFIN; ARDIARINI NOER RAHMI; KUSWANTO KUSWANTO (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Fatimah S, Ariffin, Rahmi AN, Kuswanto. 2020. Tolerance and determinants of drought character descriptors of the Madurese landrace bambara groundnut (Vigna subterranea). Biodiversitas 21: 3108-3116. Bambara groundnut (Vigna subterranea L. Verdc.) is legume of African origin overlooked in Indonesia. It has underdeveloped in Indonesia; for example, in East Java, it is only cultivated in Gresik, Lamongan, and Bangkalan of Madura. This plant can potentially be developed in dry lands, such as Madura as it has the ability to grow and develop well in a dry environment with low nutrient level. At present, there are sparse researches on the selection and determination of the drought-tolerant character descriptors of bambara groundnut in Indonesia. The present study used the expected lines of bambara groundnut selected from local lines of various regions in Indonesia using the nested design. The results showed that the drought stress treatment led to stunted growth of 12 bambara groundnut genotypes, including the number of leaves, plant height, canopy diameter, leaf thickness, number of flowers, number of stems or branches, number of internodes, length of leaf stems, root length, root wet weight, canopy wet weight, canopy dry weight, root dry weight, and leaf chlorophyll content. However, drought leads to a slight increase in the width and length of the stomata opening and leaf proline contents. The cluster analysis based on stress index and sensitivity index can classify 3 expected lines originating from Gresik Regency (G1, G2, G3), falling into the drought stress-tolerant category. Accumulated proline contents cannot be used as a descriptor of tolerance to drought stresses in bambara groundnut since the expected lines with an increase in proline contents in leaves during drought stresses based on the cluster analysis do not fall into the genotypic cluster tolerant to drought stresses.